Action in time of judicial legal provision in Ukraine - Пушняк, Олексій Віталійович (Problems of legality, 2016)
The author analyzes the temporal effect of general legal provisions created by higher judicial authorities in Ukraine. Views on the temporal effect of the latter are based on the appropriate understanding of their nature. The gradual recognition of a certain law-making value of such provisions urges the change of perceptions of their temporal effect, in particular, in terms of application of the rules on nonretroactivity to them to a certain extent. Today, however, many cases of legal provisions of higher courts have retroactive effect which is much a result of interpretation of law. Meanwhile the retroactivity of the Supreme Court opinions is limited by the period for filing petitions for reviewing of the delivereed judgments. In other cases, there are no procedural mechanisms for such review. Thus the legislation on this issue is somewhat controversial, which is one of the areas to be improved.